2013
DOI: 10.1016/j.jarmac.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The quality of children's allegations of abuse in investigative interviews containing practice narratives.

Abstract: To enhance the accuracy and completeness of children's testimony, recommendations have included implementing a practice narrative, during which children are prepared for their role as informative witnesses before discussing the allegations. In the present study, we aimed to systematically examine interviewer behaviour and the informativeness of children's testimony in a field setting. As predicted, interviewers posed fewer prompts, proportionally more open-ended prompts, and children provided proportionally mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 24 publications
4
55
0
1
Order By: Relevance
“…Although the statistical analyses were not significant, the means and effect sizes signaled that children provided more words per prompt in the substantive phase when their practice narrative contained a high proportion of open-ended questions as opposed to a low proportion. This finding is consistent with previous research that has also found that open-ended practice narratives are more effective at prompting comprehensive responses from children in the substantive phase than direct practice narratives (Price et al, 2013;Sternberg et al, 1997). We contend that a lack of significance is likely due to the limited sample size in each condition (12 and 15).…”
Section: Practice Narrativessupporting
confidence: 91%
See 2 more Smart Citations
“…Although the statistical analyses were not significant, the means and effect sizes signaled that children provided more words per prompt in the substantive phase when their practice narrative contained a high proportion of open-ended questions as opposed to a low proportion. This finding is consistent with previous research that has also found that open-ended practice narratives are more effective at prompting comprehensive responses from children in the substantive phase than direct practice narratives (Price et al, 2013;Sternberg et al, 1997). We contend that a lack of significance is likely due to the limited sample size in each condition (12 and 15).…”
Section: Practice Narrativessupporting
confidence: 91%
“…The finding that children spoke more overall when their interview contained a practice narrative echoes the results of numerous studies with non-Aboriginal children (Anderson et al, 2014;Hershkowitz, 2009;Price et al, 2013;Roberts et al, 2004;Sternberg et al, 1997;Whiting, 2013). Conversely, the null finding regarding children's words per prompt is similar to previous laboratory findings with Aboriginal children (Hamilton et al, in press a), suggesting that practice narratives may not confer benefits to the accounts of all Aboriginal children, yet they also appear to do no harm.…”
Section: Practice Narrativessupporting
confidence: 72%
See 1 more Smart Citation
“…The crucial finding was that the younger children who received a specific kind of practice were more complete than younger children in the other practice conditions. In another study, interviews with and without practice narratives were compared (Price et al 2013) in terms of the presence of interviewer prompts and open-ended questions. The authors found that in interviews containing practice narratives, interviewers asked fewer prompts and more open-ended questions than in interviews without practice narratives.…”
Section: Practicementioning
confidence: 99%
“…As stated by Lyon (2011), it is well known that the narrative practice (step ii) increases the amount of abuse disclosure information (Hershkowitz, 2009;Price, Roberts, & Collins, 2013;Sternberg et al, 1997) without impairing the accuracy of children's statements (Roberts et al, 2004). Additionally, the presentation of the "Promise to tell the truth" instruction (step iv) is mostly effective when children have been previously incited to make false reports.…”
Section: The Influence Of Social Instructions On the CI Benefitsmentioning
confidence: 99%